مستوى مساهمة معلمي السنة الخامسة ابتدائي في تنمية مهارات حل المشكلات الرياضية - فريجات, عبد الكامل; بوعامر, أحمد زين الدين (University of Eloued جامعة الوادي, 2017)
هدفت هذه الدراسة إلى التعرّف على مستوى مساهمة المعلمين في تنمية مهارة حل المشكلة الرياضية لدى تلاميذ السنة الخامسة ابتدائي, ولتحقيق هدف الدراسة استخدم الباحث المنهج الوصفي المسحي, وأعدّ بطاقة ملاحظة كأداة للدراسة, طبقت على عينة قدرها (16) معلما من معلمي السنة الخامسة ابتدائي بالمقاطعة التربوية اميه ونسه2 بولاية الوادي. وتوصّلت الدراسة الى النتائج التالية : ـ مساهمة المعلمين في تنمية مهارات حل المشكلة الرياضية ككل كان ضعيفا. ـ لا توجد فروق ذات دلالة احصائية في اسهام المعلمين في تنمية مهارات حل المشكلة الرياضية تعزى الى متغير سنوات الخدمة This study aimed to identify the level of contribution of teachers in the skill of solving mathematical problem among pupils fifth year primary development, and to achieve the goal of the study, the researcher used the descriptive survey and prepared the note card as a tool for the study, applied to a sample of (16) a teacher of teachers of the fifth year of primary schooling in the province educational Mih Ouensa 2 in wilaya d'eloued. The study found the following results: - Teachers' contribution to the development of skills to solve the mathematical problem as a whole was weak.. - No statistically significant differences in the contribution of teachers in the development of mathematical problem-solving skills are attributable to variable years of service
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: المشكلة الرياضية. ـ حل المشكلة الرياضية; mathematical problem. - Solve mathematical problem